2010
DOI: 10.1089/vbz.2009.0138
|View full text |Cite
|
Sign up to set email alerts
|

Hantaviruses and Their Hosts in Europe: Reservoirs Here and There, But Not Everywhere?

Abstract: Five hantaviruses are known to circulate among rodents in Europe, and at least two among insectivores. Four (Dobrava, Saaremaa, Seoul, and Puumala [PUUV] viruses) are clearly associated with hemorrhagic fever with renal syndrome (HFRS). PUUV, the most common etiological agent of HFRS in Europe, is carried by the bank vole (Myodes glareolus), one of the most widespread and abundant mammal species in Europe. This host-virus system is among hantaviruses also the most studied one in Europe. However, HFRS incidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
85
1
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 95 publications
(100 citation statements)
references
References 119 publications
9
85
1
5
Order By: Relevance
“…For example, Olsson et al (44) demonstrated that human cases in OctoberNovember-December are related to rodent intensity in September. Two peaks in HFRS cases are seen annually in northern countries, with a minor peak in August and a major peak in October-February (45,46). In line with previous work, we found that most cases were seen in autumn and winter (Table 3).…”
Section: Discussionsupporting
confidence: 92%
“…For example, Olsson et al (44) demonstrated that human cases in OctoberNovember-December are related to rodent intensity in September. Two peaks in HFRS cases are seen annually in northern countries, with a minor peak in August and a major peak in October-February (45,46). In line with previous work, we found that most cases were seen in autumn and winter (Table 3).…”
Section: Discussionsupporting
confidence: 92%
“…However, we were unable to detect SEOV. One potential explanation is that SEOV is only present in very focal areas, as patchy distributions are also known for other hantaviruses depending on habitat connectivity of their hosts [34]. …”
Section: Resultsmentioning
confidence: 99%
“…In spite of the large interest regarding hantavirus disease and biology, considerable gaps of knowledge still exist regarding e.g., the ecology of the viruses and how they persist in fluctuating reservoir populations. Nephropathia epidemica (NE) is a milder variant of HFRS caused by the hantavirus Puumala virus (PUUV) present in many parts of Europe (Olsson et al 2010), and bank voles (Myodes glareolus) are the natural reservoir (Brummer-Korvenkontio et al 1980, Yanagihara et al 1984. The epidemiology of NE is closely linked to the temporal and spatial dynamics of the bank vole (Niklasson et al 1995, Olsson et al 2005, Voutilainen et al 2012.…”
Section: Introductionmentioning
confidence: 99%